Pura Langgar Sebagai Wahana Dalam Mengimplementasikan Toleransi Umat Beragama Di Desa Adat Bunutin Kabupaten Bangli (Perspektif Pendidikan Agama Hindu) - Widiastuti, Ida Ayu Nyoman (Jayapangus Press, 2022)
The existence of the temple and the characteristics contained therein have Hindu religious educational values. One of them is Langgar Temple in the Bunutin Traditional Village, Bangli Regency. Pura Langgar is a type of Pura Dadia which is only held by Semeton Puri Agung Bunutin. Langgar Temple is unique in its strong values ​​of tolerance between Hinduism and Islam which can be seen from the religious activities carried out. This research was carried out to determine the existence, form of implementing religious tolerance at Langgar Temple, and the value of Hindu religious education contained in implementing religious tolerance at Langgar Temple. So this research uses a qualitative descriptive research method using existential theory, multicultural theory, and value theory. Langgar Temple can be seen in terms of structure, form, function, meaning, worshipers and people who pray at Langgar Temple. Forms of implementing religious tolerance at Langgar Temple include: providing facilities for worship, greetings, worship of religious symbols, use of pujawali ceremonial facilities, freedom of worship according to beliefs, factors encouraging and inhibiting the implementation of religious tolerance. In implementing religious tolerance at Langgar Temple, the values ​​of Hindu religious education contained in it are strong, such as: Tattwa Education Values ​​are realized with the value of sraddha, Moral Education Values ​​are realized with the value of love (Tat Twam Asi, Tri Kaya Parisudha, Wasudhaiva Kutumbhakam, Tri Hita Karana), the value of mutual cooperation (paras-paros sarpanaya, salunglung sabayantaka, sagilik-saguluk, briuk sepanggul), Ceremonial Educational Value, Aesthetic Value, and Atmanastuti Value.